Influência do tipo de medição na determinação do módulo estático de elasticidade do concreto - ARAÚJO, Suélio da Silva (2011)
The knowledge of the compressive strength and static modulus of elasticity is fundamental to the study of deformations of concrete, since deformations can cause cracks that compromise both the structural behavior of the element and serve as an entry to deleterious agents. For purposes of correlating values of compressive strength and static modulus of elasticity of concrete, cylinders were cast with different strengths, different types of strain measurements were taken, different specimen sizes and the loading speed of the testing machine. The specimens were tested at the age of 28 days to determine the compressive strength and static module of elasticity according to ABNT NBR 8522:2008, using different types of strain measurement devices: two mechanical dial indicators, surface bonded strain gages, clip gauges and LVDT (Linear Variable Differential Transducer). Two hundred and fifty eight specimens were cast with dimensions 150 mm x 300 mm and 100 mm x 200 mm using conventional normal strength concrete (NC - Class C30) and high strength concrete (HSC - Class C60). The experimental program was divided into two stages. First the static modulus of elasticity of concrete was measured to evaluate the accuracy of the method using different measuring devices and the accuracy of the method to a loading speed of 0.6 MPa/s. Then, the modulus of elasticity using different deformation measuring devices at a loading speed of 0.3 MPa/s and 0.6 MPa/s was measured. As for concrete NC and HSC, it was found that the specimens 100 mm x 200 mm obtained higher dispersion in relation to 150 mm x 300 mm specimens. In the first stage of the research, 100 mm x 200 mm specimens showed a higher dispersion when using mechanical dial gages and LVDT. The 150 mm x 300 mm NC class C30 specimens showed greater dispersion when using in mechanical dial gages and external strain gages. However, the HSC showed higher dispersion when mechanical dial gages and LVDT were used. In both concretes tested, the mechanical dial gages showed greater dispersion. In the second stage of the research, 150 mm x 300 mm specimens tested at the loading speed of 0.3 MPa/s showed greater dispersion when electrical strain gages and clip gauges were used. The 150 mm x 300 mm specimens tested at loading speed of 0.6 MPa/s showed greater dispersion when electrical strain gages and mechanical dial gages were used.